2016
DOI: 10.1371/journal.pone.0155806
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Bacterial Resistance of Therapeutically Nonequivalent Generics: The Case of Piperacillin-Tazobactam

Abstract: Previous studies have demonstrated that pharmaceutical equivalence and pharmacokinetic equivalence of generic antibiotics are necessary but not sufficient conditions to guarantee therapeutic equivalence (better called pharmacodynamic equivalence). In addition, there is scientific evidence suggesting a direct link between pharmacodynamic nonequivalence of generic vancomycin and promotion of resistance in Staphylococcus aureus. To find out if even subtle deviations from the expected pharmacodynamic behavior with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
1
9
0
1
Order By: Relevance
“…The neutropenic murine infection model has recently been used to compare the therapeutic equivalence of generic molecules with respect to innovator piperacillin-tazobactam (Rodriguez et al, 2016). Although a generic in that study did not achieve good results and favored the amplification of resistant microorganisms, the other generics evaluated, including the one analyzed in the present study, showed the same performance as the innovator, supporting the lack of differences in the clinical outcomes in this study (Rodriguez et al, 2016).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The neutropenic murine infection model has recently been used to compare the therapeutic equivalence of generic molecules with respect to innovator piperacillin-tazobactam (Rodriguez et al, 2016). Although a generic in that study did not achieve good results and favored the amplification of resistant microorganisms, the other generics evaluated, including the one analyzed in the present study, showed the same performance as the innovator, supporting the lack of differences in the clinical outcomes in this study (Rodriguez et al, 2016).…”
Section: Discussionsupporting
confidence: 64%
“…The safety and therapeutic equivalence of generic antibiotics is a controversial issue. However, the data from this study, along with real-world evidence, indicate that its use can be as safe and effective as the innovator, which has been demonstrated for other antimicrobials and other infections, and for different indications, such as cardiovascular (McCormack and Chmelicek, 2014;Rodriguez et al, 2016;Lin et al, 2016;Kesselheim et al, 2016;Jackevicius et al, 2016). In addition, economic analyses have shown that generic antibiotic treatments during a 5-day hospitalization cost on average US$ 45.5-98.2, while the use of innovators can cost US$ 106.2-463.7.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Rodriguez et al 20 have compared the in-vitro activity of an innovator and a generic piperacillintazobactam in a study aimed to determine the impact of therapeutically non-equivalent generics on bacterial resistance. Though there was no significant difference in MIC value for both innovator and generic products, therapeutic non-equivalence was observed in the in-vivo assessment and higher enrichment of resistant sub-populations when exposed to the generic products.…”
Section: Assessment Of the Efficacy Of Generic Parenteral Products Bymentioning
confidence: 99%
“…Besides since the particle size of the bulk powder of all imported meropenems is larger than that of the brand drug, this was identified as the cause of being less likely to dissolve. Furthermore, it was reported that generic Piperacillin/ Tazobactam was pharmaceutic difference and therapeutically nonequivalence [5,6]. A generic product is approved as a drug as long as its main ingredient is the same as that of the original drug.…”
Section: Introductionmentioning
confidence: 99%